КОНЦЕПТУАЛЬНІ ОСНОВИ ГАРМОНІЗАЦІЇ ОСВІТНІХ СИСТЕМ В КОНТЕКСТІ ПРОФЕСІЙНОЇ ПІДГОТОВКИ МАЙБУТНЬОГО УЧИТЕЛЯ (Педагогіка вищої та середньої школи, 2009)
In article the problem of the coordinated functioning of educational systems which define quality of preparation of the future teachers is analyzed. To number of key positions by the author are carried a mood of social systems on open multichannel interaction and innovative strategy of development. It is underlined that harmonization of educational system and the person occurs at level of conceptual self - determination of the future teacher.